Neoplasm Risk in Patients With Rheumatoid Arthritis Treated With Fostamatinib: A Systematic Review and Meta-analysis - Chen, Yuehong; Liu, Huan; Tian, Yunru; Luo, Zhongling; Yin, Geng; Xie, Qibing (Frontiers in Pharmacology, 2022)
Background: This study aimed to assess neoplasm risk in patients with rheumatoid arthritis (RA) treated with fostamatinib. Methods: Studies were collected from electronic databases of OVID Medline, OVID EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science. We included studies that reported neoplasms in patients with RA treated with fostamatinib. Studies were selected separately, and study selection was repeated by two reviewers based on the study selection criteria. Data were collected, and methodological quality assessment was performed. Data were pooled using the Peto odds ratio (OR) with a 95% confidence interval (CI). Subgroup analyses of the fostamatinib dose, trial duration, neoplasm nature, and neoplasm-originating systems were conducted. A funnel plot was used to estimate publication bias, and sensitivity analysis was performed to test the robustness of the results. Results: Seven trials involving 4,971 participants showing low to moderate risk of bias were included. Compared with the placebo, fostamatinib use was not associated with the risks of overall neoplasms (Peto OR=2.62, 95%CI 0.97-7.10), malignant neoplasms (Peto OR=3.08, 95%CI 0.96-9.91), or benign neoplasms (Peto OR=1.71, 95%CI 0.26-11.36). Nevertheless, compared with the placebo, a longer duration of fostamatinib use had a higher risk of malignant neoplasms (Peto OR=4.49, 95%CI 1.03-19.60) at 52 weeks. As for malignant neoplasms in the digestive system, lower doses of fostamatinib reduced the neoplasm risk (100mg bid vs 150mg qd: Peto OR=0.06, 95%CI 0.01-0.59). Sensitivity analysis showed no significant differences in the effective trends, and no publication bias was found. Conclusions: Fostamatinib is not associated with the risks of overall neoplasms as compared to placebo. Nevertheless, a longer duration of fostamatinib use may be associated with a risk of malignant neoplasms and higher doses of fostamatinib may increase malignant neoplasms in the digestive system. Further well-planned cohort studies with a larger study population are needed to elucidate these outcomes.